UPAYA PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI MATERI MEMECAHKAN MASALAH MEMBACA DATA STSTISTIK DALAM MATA PELAJARAN EKONOMI MELALUI MODEL PEMBELAJARAN JIGSAW, KELAS X IPS 2 SEMESTER GANJIL DI SMA NEGERI 3 KOTABUMI TAHUN PELAJARAN 20 - emawati emawati (Eksponen, 2020)
SMA Negeri 3 Kotabumi as an educational institution has the problem of still low student learning outcomes in Economics. Student learning outcomes in economic subjects, especially students of class X IPS 2 are still low. Determination of learning strategies in order to improve the quality of the process and learning outcomes can be investigated by classroom action research, because this study aims to overcome problems or solve problems in the classroom by taking action. One of the cooperative learning techniques is the Jigsaw technique. By implementing Cooperative Learning procedures correctly, it will be able to activate students so that they can improve student learning outcomes Classroom Action Research (CAR) is designed as a study material in the application of learning "Jigsaw" models to improve the ability to solve statistical problems in Economics. This class action research was conducted on students of class X IPS 2 of SMA Negeri 3 Kotabumi in the odd semester of 2018/2019, with 32 students consisting of 15 boys and 17 girls. This research has the benefit of increasing the ability of students to understand economics in this case students are trained to dare to express opinions or differ opinions on issues of presenting data. Learning with the jigsaw model can be presented to improve the ability to understand statistics in Economics. The study design was carried out in two cycles, starting with planning, implementing actions, observing, reflecting, and continuing with the next planning cycle. This research took place in September 2018 until November 2018. Based on the results of the study it was concluded that the Jigsaw model was able to improve the learning outcomes of Economics in class X IPS 2 students of SMA Negeri 3 Kotabumi in the academic year 2018/2019.